Arabidopsis MED18 Interaction With RNA Pol IV and V Subunit NRPD2a in Transcriptional Regulation of Plant Immune Responses - Zhang, Yan; Shi, Chengchen; Fu, Weihong; Gu, Xiaojing; Qi, Ziyang; Xu, Weizhong; Xia, Gengshou (Frontiers in Plant Science, 2021)
Mediator is a conserved multiprotein complex important for transcription by RNA polymerase II (Pol II). Arabidopsis Mediator subunit MED18 regulates flowering, hormone signaling and plant immunity. Here we report that Arabidopsis MED18 interacted with NUCLEAR RNA POLYMERASE D2a (NRPD2a), the second largest subunit of the nuclear Pol IV and V, which function in RNA-directed DNA methylation and epigenetic regulation of gene expression. Mutants for both MED18 and NRPD2a were compromised in resistance to necrotrophic fungal pathogen Botrytis cinerea. Mutants for NRPD1a, the largest subunit of Pol IV, were also compromised in resistance to Botrytis, supporting a critical role of Pol IV and V in plant defense against Botrytis. Increased Botrytis susucepibility of both the med18 and nrpd2a mutants were associated with reduced accumulation of reactive oxygen species, which are known to promote resisitance to Botrytis. Both the basal and pathogen-induced levels of salicylic acid and jasmonic acid were also significantly altered in the the med18 and nrpd2a mutants. Transcriptome profiling found that MED18 and NRPD2a affected both unique and overlapping sets of genes in a broad spectrum of biological processes and pathways that influence plant-pathogen interaction. The genes altered in expression in the med18 and nrpd2a mutants include disease resistance proteins, salicylic acid and jasmonic acid signaling and responses, which are known to affect resistance to necrotrophic pathogens. The novel interaction between subunits of Mediator and plant-specific RNA polymerases provides a new mechanism for epigenetic regulation of resistance and expression of defense-related genes in plant immunity.